The Use of Mobility Devices and Personal Assistance: A Joint Modeling Approach - Hongdao Meng PhD, MPH; Lindsay J. Peterson PhD; Lijuan Feng PhD; Debra Dobbs PhD; Kathryn Hyer MPP, PhD (Gerontology and Geriatric Medicine, 2019)
Objective: To examine whether mobility device use substitutes for personal assistance among U.S. older adults. Method: Using the National Health and Aging Trends Study, we identified 3,211 community-living older adults (aged 65 and older) who reported mobility difficulties at baseline. We used recursive bivariate probit models to simultaneously estimate the effect of covariates on the likelihood of using (a) mobility devices and (b) personal assistance to accommodate mobility difficulty. Independent variables included age, gender, race, physical/mental health status, cognition, and comorbidities. Results: Predictors of the use of personal assistance and mobility devices exhibit important similarities and differences. Device use reduced the odds of receiving personal assistance by 50% (odds ratio [OR] = 0.50, 95% confidence interval [CI] = [0.29, 0.86]). Discussion: Findings suggest device use substitutes for personal assistance. Practitioners and policymakers should promote the appropriate use of mobility devices while recognizing the importance of assistance with some groups and the potential of increasing mobility device use.